2023
DOI: 10.1146/annurev-psych-032720-040512
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Color Perception and Cognition

Abstract: Color is a pervasive feature of our psychological experience, having a role in many aspects of human mind and behavior such as basic vision, scene perception, object recognition, aesthetics, and communication. Understanding how humans encode, perceive, talk about, and use color has been a major interdisciplinary effort. Here, we present the current state of knowledge on how color perception and cognition develop. We cover the development of various aspects of the psychological experience of color, ranging from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 143 publications
0
15
0
Order By: Relevance
“…Interestingly, experience appears to play a significant role in chromatic and luminance sensitivity as suggested in studies comparing premature to full-term infants (Bosworth & Dobkins, 2013). While variations in sensitivity appear to occur at around 4 months, when actual comprehension of a scene takes place is not known (Maule et al, 2023). Preference for colors may initiate as a sensory bias represented by longer gaze behaviors associated with different hues and evolve into hedonic or aesthetic interpretations when significant interactions with environmental features increase (Maule et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, experience appears to play a significant role in chromatic and luminance sensitivity as suggested in studies comparing premature to full-term infants (Bosworth & Dobkins, 2013). While variations in sensitivity appear to occur at around 4 months, when actual comprehension of a scene takes place is not known (Maule et al, 2023). Preference for colors may initiate as a sensory bias represented by longer gaze behaviors associated with different hues and evolve into hedonic or aesthetic interpretations when significant interactions with environmental features increase (Maule et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…A variety of researchers have addressed the use of color in healthcare facilities for children as part of a broad analysis of the space (e.g., Abu Lawi, 2017;Abulawi, et al, 2019). While the preponderance of color studies with children may be a result of color's role in enabling cognitive development (per Maule et al, 2023), evidence suggests that the preferences of children are similar to those of adults (Child, et al, 1968). Coad and Coad (2008) found children aged 3-18 that had experience in hospitals expressed a broad preference for blue-green.…”
Section: Color Studies In General Medical Settingsmentioning
confidence: 99%
“…Here, we evaluated the influence of memory on infants’, children's, and adults’ sensitivity to differences in the saturation of brightly colored stimuli. To do so, we designed an infant‐friendly, gaze‐contingent eye‐tracking procedure that exploits the basic perceptual tendency of humans, without training and regardless of age, to be drawn to look at more saturated (vs. less saturated) stimuli (Maule, Skelton, & Franklin, 2022; Werner & Wooten, 1979). This perceptual judgment task allowed us to test whether and how participants’ abilities to discriminate the relative saturation levels of sequentially presented stimuli would be influenced by their accumulated experience with the task.…”
Section: Introductionmentioning
confidence: 99%
“…In all cases, the colour cards were shown by an examiner who assessed detectability based on the infant's fixation behaviour observed through a peephole in the centre of the screen. With different studies also based on forced-choice preferential looking paradigm, Knoblauch and col. and other authors found a later age of maturation of colour discrimination after 10 years of age or even later 22,23. In all these studies assessment of correct discrimination was performed manually by an examiner and the duration of each exam varied between 10 and 20 min.…”
mentioning
confidence: 98%